Peran Strategic Agility Dalam Meningkatkan Kinerja UMKM Di Era Digital - Desta Rismawati; Ana Samrotul Fuadah; Siti Maisaroh Maisaroh; Vicky F Sanjaya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut NYak Dhien, 2025)
This study aims to investigate how strategic agility can enhance the performance of micro, small, and medium enterprises (MSMEs) in the digital era. The study employs a qualitative method using survey techniques. Data were collected through questionnaires distributed to MSMEs in Bandar Lampung. The instruments used include observation guidelines and questionnaires designed to analyze the relationship between strategic agility and MSME performance, as well as the factors influencing them. The findings reveal that strategic agility significantly contributes to MSME performance improvement, accounting for 51.7% when supported by digital technology. The study also identifies that leveraging digital technology, product innovation, and quick responses to market changes are key elements in enhancing MSME competitiveness. In conclusion, the study underscores the importance of implementing strategic agility in MSMEs’ digital transformation to improve performance and competitiveness. These findings provide valuable insights for MSMEs, governments, and stakeholders to address challenges and support the digital transformation of the MSME sector.